Age‐related changes in appendicular lean mass in males with Duchenne muscular dystrophy: A retrospective review. Issue 2 (7th December 2020) - Summer, Suzanne S.; Wong, Brenda L.; Rutter, Meilan M.; Horn, Paul S.; Tian, Cuixia; Rybalsky, Irina; Shellenbarger, K. Courtney; Kalkwarf, Heidi J.
Abstract: Background: Appendicular lean mass (ALM) trajectory in males with Duchenne muscular dystrophy (DMD) has potential applicability for treatment and research and has not been characterized. Methods: This chart review included longitudinal data on 499 males with DMD receiving glucocorticoids and 693 controls, ages 5 to 22.9 y. ALM (kg) was measured by dual energy x‐ray absorptiometry (DXA). Appendicular lean mass index (ALMI, kg/m 2 ) was calculated for height adjustment. Reference centiles were generated using data from healthy controls, and ALM and ALMI Z‐scores were calculated for patients with DMD. Generalized linear models were used to estimate median Z‐scores by age and functional mobility status (FMS) score. ALM velocity by age was modeled using superimposition, translation and rotation (SITAR). Results: Compared to controls, males with DMD had lower ALM from an early age. ALMI Z‐scores dropped below 0 at age 8 y or FMS of 2, and below −2.0 at age 13 y or FMS of 3 ( P < .05). Age at peak ALM velocity was similar in both groups, but the magnitude was higher in controls (3.5 vs. 0.7 kg/y, P < .0001). Patients with DMD had a transient loss of ALM around age 12 y, an increase at age 14 y, then a further decline at age 16 y, remaining low thereafter. Conclusions: Males with DMD have progressive decline in lean mass with age and worsening functional mobility. DXA measurement of ALM may be useful for monitoring lean mass status in patients with DMD, providing valuable information for individual treatment plans and research endeavors.